2006
DOI: 10.1002/j.2161-1912.2006.tb00026.x
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Phase in the Development of the International Student Supervision Scale

Abstract: This study outlines the development of a scale designed to measure supervisory issues unique to international students. A factor analysis yielded a 1-factor scale that showed good internal consistency and was correlated with supervisees' acculturation level, satisfaction with supervision, and supervisors' sensitivity to diversity issues. Implications for supervision are addressed.Este estudio resume el desarrollo de una escala diseñada para medir los asuntos de supervision unicos a estudiantes internacionales.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 17 publications
5
44
2
1
Order By: Relevance
“…Based on our findings and other findings in the literature on the influence of multicultural discussion on other supervision related variables (e.g., Mori et al 2009;Nilsson and Dodds 2006), we support the construct of multicultural discussion in supervision as being valid and important to the understanding of multicultural and cross-cultural supervision.…”
Section: Multicultural Discussion In Supervisionsupporting
confidence: 75%
See 2 more Smart Citations
“…Based on our findings and other findings in the literature on the influence of multicultural discussion on other supervision related variables (e.g., Mori et al 2009;Nilsson and Dodds 2006), we support the construct of multicultural discussion in supervision as being valid and important to the understanding of multicultural and cross-cultural supervision.…”
Section: Multicultural Discussion In Supervisionsupporting
confidence: 75%
“…SCK comprises three items, and assesses supervisees' perceptions of their multicultural knowledge in comparison to their supervisors' perceptions. Nilsson and Dodds (2006) reported an internal consistency of .94 for MD and .58 for SCK. Due to low reliability, the developers recommended that only the MD subscale be used.…”
Section: International Student Supervision Scale (Isss)mentioning
confidence: 95%
See 1 more Smart Citation
“…Communication was a theme common to Treloar et al 's (2000) study of international medical students at an Australian university; they found that students' communication issues were compounded by strong local accents. The associated patient usage of slang also impacts international students' clinical progress (Mori et al 2009;nilsson and dodds 2006).…”
Section: International Allied Healthcare Students' Clinical Experiencesmentioning
confidence: 99%
“…Guanipa (2002) developed an instrument that assesses attention given by supervisors to multicultural issues in supervision. Likewise, Nilsson and Dodds (2006) developed the International Student Supervision Scale, which assesses issues that affect international students, such as challenges in speaking or understanding English and learning the US culture. Other work has focused on sexual orientation in supervisioneither fostering sexual minority supervisees' skills (Pfohl 2004) or how to supervise cases involving sexual minority clients (Halpert et al 2006;Long and Lindsey 2004).…”
mentioning
confidence: 99%